Soil carbon storage potential of Awat-Awat Mangrove Forest Reserve at Lawas, Sarawak, Malaysia - Mohamad Pazi, Ahmad Mustapha (2017)
Mangrove forest is one of the most important ecosystems to act as carbon pools. The assessment of soil carbon storage has been done in many places, but there is still a lack of data about the estimation of soil carbon storage in Awat-Awat Mangrove Forest Reverse Lawas, Sarawak. The general objective of this study was to assess the soil carbon storage potential in Awat-Awat Mangrove Forest Reserve Lawas, Sarawak and the specific objectives were to determine the soil physiochemical properties under six dominant mangrove tree species by soil depth; to compare the soil physiochemical properties between the seasons, mangrove zones, and soil depths and to estimate the total of soil carbon pools potential in the mangrove soil. In this study, six dominant mangrove tree species were found in three different zones and there are Sonneratia alba, Sonneratia caseolaris, Rhizophora apiculata, Rhizophora mucronata, Lumnitzera littorea and Xylorcarpus granatum. Six study plots (50 m  50 m) were established randomly based on dominant mangrove tree species in the study area. A total of 300 soil samples were collected in November and December 2014 (wet season) and March and April 2015 (dry season). The soil physiochemical properties under six dominant mangrove tree species by soil depth were determined. In term of the soil physiochemical properties between the seasons, mangrove zones, and soil depths, data were calculated to compare between the factors. The total of the mass of soil carbon pools in 4372 ha of Awat-Awat Mangrove Forest Reserve was also estimated in this study. As a result, the soil physiochemical properties under six dominant mangrove tree species by soil depth showed the soil texture at Sonneratia alba soil was sandy clay loam at all depths. While, Sonneratia caseolaris soil was sandy clay loam in the soil depth (0-30 cm) and sandy loam in the soil depth (30->100 cm). Rhizophora apiculata and Rhizophora mucronata soils were sandy clay loam in the soil depth (0-15 cm) and sandy loam in the soil depth (15->100 cm). The soil texture in Lumnitzera littorea and Xylorcarpus granatum were sandy loam. The soil bulk density, showed the Sonneratia alba soil was highest among the other species and the deepest soil were found significantly different among the other soil depth with mean of 1.273a(±0.005) g cm-3. The soil pH of this area was acidic and deepest soil pH showed the lowest pH. The soil organic matter (SOM) and total organic carbon (TOC) were significantly highest under the Rhizophora apiculata species in the deepest soil depth 30.88a(±1.56)% and 17.91a(±0.91)%. Meanwhile, the total mass of soil carbon (CT) was significantly highest under Rhizophora mucronata in the deepest soil depth 235.66a(±5.37). In term of the seasons, soil texture of mangrove soil was sandy loam and the sand content was significantly higher during the wet season than the dry season, the silt and clay contents were significantly highest during the dry season than the wet season. For the soil bulk density, showed no significant different between the seasons. The mean comparison of the soil pH between the seasons showed significantly different and dry season showed higher values than the wet season. The soil organic matter (SOM) and total organic carbon (TOC) were obtained the higher result during the wet season with 18.30a(±0.67) and 10.60a(±0.39). The mean comparison of (SOM) and (TOC) showed significantly different between the seasons. In term of mangrove zone, the soil texture at the seaward was sandy loam, middleward was sandy clay loam and landward was sandy loam. For the soil fractions between the zones, the sand content was significantly highest in the landward zone, silt content was highest at the landward but there is no significantly among the other zones and the clay content was significantly highest at the middleward zone. For the value of the soil bulk density, the seaward zone has recorded the highest value with 1.145a(±0.009) g cm-3 and the mean comparison was showed significantly different among the zones. The soil pH in the mangrove zone was acidic and showed the seaward zone was obtained the highest value. The mean comparison of soil pH showed significantly different among the zones. The middleward zone obtained the highest percentage of SOM and TOC with 25.93a(±0.403)% and 15.04a(±0.23)%. The mean comparison of the SOM and TOC showed significantly different among the zones. In term of soil depth, the soil texture was sandy loam. The soil fractions showed the sand and silt contents were significantly highest in the soil depth D4 (50-100 cm) and clay content was significantly highest in the soil depth D1 (0-15 cm). The soil bulk density, soil depth D5 (>100 cm) obtained the highest value and give a significantly different among the soil depths. For the soil pH in soil depth was acidic and the soil depth 1 (0-15 cm) obtained the highest value of soil pH. The mean comparison of soil pH between the soil depth was showed significant different. The percentage of soil organic matter (SOM) and total organic carbon (TOC) in soil depth, soil depth D5 (>100 cm) was obtained the highest percentage with a mean 18.88a(±1.01)% and 10.95a(±0.59)%. The mean comparison was showed significantly different among the soil depths. The estimated of soil carbon pools potential of the Awat-Awat Mangrove Forest Reserve Lawas, Sarawak has been done and the total of soil carbon mass in 4372 ha of mangrove forest was 1666431.52 t C. As a conclusion, Awat-Awat Mangrove Forest Reserve has a potential as soil carbon pools regarding on the result of SOM, TOC and CT were give a significantly result in estimated of soil carbon pools. As a recommendation, this forest should be conserved to maintain this potential areas as carbon pools in the future and need a further study to monitor the soil carbon changes in this mangrove from time to time.